Un baúl de tips y reglas ortográficas. Propuesta de enseñanza y aprendizaje de la ortografía desde una perspectiva comunicativa y funcional - Acevedo Quintero Sara Juliana (Universidad Antonio Nariño, 2024)
This degree work entitled “A trunk of spelling tips and rules. A proposal for teaching and learning spelling from a communicative and functional perspective” presents the development of a pedagogical proposal for teaching and learning spelling from a communicative perspective. Therefore, from the action research approach, the pedagogical proposal “A trunk of spelling tips and rules” is carried out with eighth grade students of the Liceo Los Angeles school (Bogota), to favor the learning of spelling from a communicative and functional perspective. This allowed students to understand the place of spelling, not as an isolated and memorized subject, but as an element that favors and strengthens skills such as reading and writing in real communication situations.